Aplication of Azolla pinnata and N-Fixing Endophytic Bacteria To Enhance Chemical, Plant Properties, and Dry Weight Corn Plant at Inceptisols Jatinangor - Mieke Rochimi Setiawati; Pujawati Suryatmana; Yuliati Machfud; Yori Tridendra (Agrologia, 2019)
The research to determine the effect of Azolla pinnata dry weight and nitrogen-fixing endophytic bacteria on the chemical properties of soil and plants and the growth of corn plants on Inseptisols from Jatinangor. This experiment was carried out in the greenhouse of the Faculty of Agriculture, Padjadjaran University, Jatinangor, West Java. The experiment design was Randomized Block Design (RDB) in factorial pattern consisted of two factors and three replications. The first factor was dosage of Azolla pinnata compost consisted of four levels (0 g pot-1, 12.5 g pot-1, 25 g pot-1, 37.5 g pot-1). The second factor was nitrogen-fixing endophytic bacteriaconsisted three levels: without nitrogen-fixing endophytic bacteria, just used nitrogen-fixing endophytic bacteria Acinetobacter sp., used nitrogen-fixing endophytic bacteria Pseudomonas sp. The results showed that there were interactions between Azolla pinnata and N2-fixing endophytic bacteria on N concentration and N uptake of corn plants. Applicaton Azolla pinnata compost with a dosage of 37.5 g pot-1 equivalent to 6 tons ha-1 can produce the highest dry weight of corn plants. Both nitrogen-fixing endophytic bacteria and azolla compost have not been able to increase the total N of Jatinangor Insepticols.Keywords: Azolla pinnata, nitrogen-fixing endophytic bacteria, Acinetobacter sp.,   Pseudomonas sp., corn plant